Delastria, A NEW GENUS OF HYPOGEOUS FUNGI RECORD FOR THE TURKISH MYCOBIOTA - Bekir Çöl; Emre Keskin; Ergin Sahin; İsmail Şen; Ilgaz Akata (Trakya University Journal of Natural Sciences, 2023)
In the present study, fungal samples collected from Enez and Süloğlu districts of Edirne Province, in Türkiye with the help of truffle-detecting dogs were analyzed. The macroscopic features and environmental details of the collection sites were documented in their natural habitats. The samples were investigated with light- and scanning electron microscopy (SEM) and were also used in ITS rDNA-based molecular phylogenetic analysis, which revealed that they belong to Delastria rosea Tul. amp; C. Tul. The identification was further supported by morphological data. This is the first record of D. rosea in Türkiye at the genus and species level. A brief description of the newly reported species is provided. Macro- and microphotographs of the spores taken by both ligth and electron microscop (SEM). With this study, the number of genera and species of Turkish truffles and truffle-like fungi has increased to 36 and 105, respectively.